2009
DOI: 10.1016/j.chemgeo.2009.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical transformations controlling acid mine drainage chemistry

Abstract: The role of Fe(III) minerals in controlling acid mine drainage (AMD) chemistry was studied using samples from two AMD sites [Gum Boot (GB) and Fridays-2 (FR)] located in northern Pennsylvania. Chemical extractions, X-ray diffraction (XRD), scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy (FTIR) were used to identify and characterize Fe(III) phases. The mineralogical analysis revealed schwertmannite and goethite as the principal Fe(III) phases in the sediments. Schwertmannite part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 29 publications
3
43
0
Order By: Relevance
“…Under acidic conditions, the transformation of schwertmannite to goethite may occur over periods of several years (5,30,40), while at circumneutral pH, the reaction may occur over periods of 100 days (57). Recent work by Burton et al (10,11) has suggested that Fe(II) enhances the schwertmannite-to-goethite transformation, with the Fe(II)-enhanced reaction occurring over periods of hours.…”
Section: Formation Of Magnetic Fes Phasesmentioning
confidence: 99%
“…Under acidic conditions, the transformation of schwertmannite to goethite may occur over periods of several years (5,30,40), while at circumneutral pH, the reaction may occur over periods of 100 days (57). Recent work by Burton et al (10,11) has suggested that Fe(II) enhances the schwertmannite-to-goethite transformation, with the Fe(II)-enhanced reaction occurring over periods of hours.…”
Section: Formation Of Magnetic Fes Phasesmentioning
confidence: 99%
“…This release of sulfate may be due to the reductive solubilization of sulfatecontaining Fe(III) phases. Schwertmannite (Fe 8 O 8 (OH) 8-2x (SO 4 ) x nH 2 O, where 1 B x B 1.5) is sulfate-containing Fe(III) phase that is frequently encountered in AMDimpacted systems (DeSa et al 2010;Murad and Rojík 2005;Peretyazhko et al 2009;Regenspurg et al 2004;Schwertmann et al 1995). Such minerals form in acidic, sulfate-rich fluids when sulfate ions are incorporated into the mineral structure (Bigham et al 1990(Bigham et al , 1996Gagliano et al 2004;Murad and Rojík 2005).…”
Section: Effects Of Algal Organic Carbon On Fe and S Cyclingmentioning
confidence: 98%
“…The pH of formaldehyde-deactivated incubations decreased, likely due to acidity associated with Fe(III) phases. For instance, Peretyazhko et al (2009) have suggested that Fe(III) phases (e.g. schwertamannite) in AMD-impacted systems may exert considerable control on the pH of fluids, regardless of the initial chemical composition of those fluids.…”
Section: Effects Of Algal Organic Carbon On Fe and S Cyclingmentioning
confidence: 99%
“…in these precipitates by up to 61 mg/g. Other potential As scavengers in mine drainage areas include ferrihydrite (Fe(OH) 3 ), which is often present as an intermediate product of schwertmannite transformation to goethite (Peretyazhko et al 2009), and has been demonstrated to have a higher As retention affinity due to its higher surface area (Carlson et al 2002). Romero et al (2010) found that presence of hematite (Fe 2 O 3 ), goethite (FeOOH), or magnetite (Fe 3 O 4 ) in mine water can substantially reduce As content in schwertmannite-absent localities.…”
Section: A(d/b)sorption Processesmentioning
confidence: 99%